Analysis of Hazard Risk Understanding Using "Safety-Uno" Education Media for Batik Workers in Batik X and the General Public - Hasibuan, Athiyyah Qurrotu'ain; Mei, Aura Sasi; Amrullah, Farhan Dani; Rahma, Fitra Aulia; Rasyad, Mohamad Hanif; Shah, Muhammad (Journal of Safety Education, 2024)
Batik is the art of drawing on cloth using canting with small ends and batik wax. The process of making batik can cause work accidents and occupational diseases that occur because of equipment failure and human errors that do work not according to procedures. However, in the informal batik industry, there still needs to be more knowledge and awareness related to potential hazards and controls that must be carried out. Therefore, it is necessary to conduct education to increase workers' understanding and create a safe and comfortable work environment. This research method is a quantitative study using the Wilcoxon Test to compare observations before and after treatment and determine the effectiveness of treatment. Based on the observations and analysis that have been carried out, it can be concluded that there is a significant relationship between the use of safety cards.